Befriending the Beloved Disciple: A Jewish Reading of the Gospel of John. By Adele Reinhartz - Bond, Helen K. (The journal of theological studies, 2008)
How does who we are as human beings affect the way in which we interpret texts, especially if they critique or disparage groups, practices, or doctrines with which we might identify, or which seem unethical? These are the questions which guide Adele Reinhartz's engaging and highly readable short study of John's gospel. In response, she offers four reading strategies with which she, as a Jewish female professor of New Testament, might want to approach the gospel: compliant, resistant, sympathetic, and engaged. The gospel, she argues, contains three distinct but interrelated stories (the historical story of Jesus; the cosmological story; and the story of John's community), and each reading strategy engages with these three stories in turn.